2023
DOI: 10.1093/pnasnexus/pgad296
|View full text |Cite
|
Sign up to set email alerts
|

Ocean emission of microplastic

Daniel B Shaw,
Qi Li,
Janine K Nunes
et al.

Abstract: Microplastics are globally ubiquitous in marine environments, and their concentration is expected to continue rising at significant rates as a result of human activity. They present a major ecological problem with well-documented environmental harm. Sea spray from bubble bursting can transport salt and biological material from the ocean into the atmosphere, and there is a need to quantify the amount of microplastic that can be emitted from the ocean by this mechanism. We present a mechanistic study of bursting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…Observational extrapolation, marked red, suggests global fluxes for microplastics under 140 μm, slightly over our sub-100 μm focus . As for the bottom-up calculations marked in black, they appear to fall within the upper limit. , However, the emission fluxes reported by Shaw et al for microplastics within the 200 mm size range are much over our sub-100 μm focus, and as they stated, just emitted from the ocean surface, not the flux of microplastics that can suspended for a relatively longer time in the atmosphere …”
Section: Theoretical Upper Limit Of Global Microplastic Sea–air Emiss...supporting
confidence: 54%
See 2 more Smart Citations
“…Observational extrapolation, marked red, suggests global fluxes for microplastics under 140 μm, slightly over our sub-100 μm focus . As for the bottom-up calculations marked in black, they appear to fall within the upper limit. , However, the emission fluxes reported by Shaw et al for microplastics within the 200 mm size range are much over our sub-100 μm focus, and as they stated, just emitted from the ocean surface, not the flux of microplastics that can suspended for a relatively longer time in the atmosphere …”
Section: Theoretical Upper Limit Of Global Microplastic Sea–air Emiss...supporting
confidence: 54%
“…These modeling estimates highlight challenges in scaling globally without the benefit of high-resolution observations, and oversimplifying factors in particle long-range atmospheric transport. 42 Finally, some studies began adopting a bottom-up approach, calculating the oceanic microplastic emission using the 26 which is 10 4 times lower than the previous megatons/year-level estimates 30,31,32 34 These laboratory works could have their potential drawbacks, such as (1) the laboratory conditions cannot cover all conditions over the oceans and (2) airflow entering the SSA production chamber typically under 10 L/min, insufficient to generate realistic strong turbulence in marine atmosphere, causing SSA larger than 10 μm to quickly deposit, might resulting in significant losses and potentially underestimating microplastic flux. Nevertheless, these bottomup calculated fluxes are significantly lower than those in previous estimates.…”
Section: Controversy On Microplastic Sea−air Emission Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, and during the course of this work, laboratory studies have confirmed transfer of plastic from water to air in bubble bursting processes for particle of size 300 nm and larger. 18,30–35 Bubble bursting has been studied from waters ranging from fresh to saline and air entrainment has been mimicked in different ways. Most studies have addressed particles made of polystyrene (PS), polypropylene (PP) and polyethylene (PE) which are among the plastic polymers produced in the highest amount 36 and identified in both sea 37 and lake 21 water.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, while the studies mentioned above have deployed bubble plumes, Shaw et al 35 demonstrated and quantified transfer of PE particles in the size range of 10 to 280 μm (diameter) in a single bubble system. Here bubbles escape from a needle and ascend in liquids with different densities (deionized water, artificial seawater with a salinity of 42 g kg −1 and ethanol), all with a small amount of the surfactant SDS added.…”
Section: Introductionmentioning
confidence: 99%